(untitled) (Forum Penelitian Agro Ekonomi, 2024)
Inclusion of Indonesia in the ASEAN Single Market can be seen as opportunities and challenges for the national food resiliency. Results of the study shows that Indonesia was sufficient in food availability, moderate in food accessibility, low in food utilization, and relatively unstable in food price. To improve its food resiliency in the region, it is advisable for Indonesia to carry out some strategic steps as follows: (1) improving food self-resiliency, (2) developing local foods, (3) improving market access, and (4) improving cooperation in food security. The needed support policies were: (1) continuing efforts to increase sustainable food production, (2) developing local food industries, (3) promoting local food products, (4) improving infrastructures, logistics system, supply chain, as well as institutions and market information systems, (5) standardization of food quality and safety, (6) establishing collaboration in regional food security, and (7) managing regional food trade to achieve food resiliency.